2005
DOI: 10.1038/sj.tpj.6500301
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Parkinson's disease is related to a genetic polymorphism of the cannabinoid receptor gene (CNR1)

Abstract: Depression is a common symptom in Parkinson's disease (PD) and it is present in up to 40% of the patients. The cause of depression in PD is thought to be related to disturbance of monoamine neurotransmission. The endogenous cannabinoid system mediates different brain processes that play a role in the control of behaviour and emotions. Cannabinoid function may be altered in neuropsychiatry diseases, directly or through interactions with monoamine, GABA and glutamate systems. For this reason, we have investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 49 publications
1
81
0
5
Order By: Relevance
“…In the design of this study, we have explicitly set the aim to investigate CB 1 receptor network alterations by using both absolute and relative [ 18 F]MK-9470 measurements. It is known that there is a higher physiologic interindividual variability of absolute regional [ 18 F]MK-9470 determinations in the human brain, in the order of several tens of per cent [14,57]. Relative measurements have the advantage of being much more sensitive, allowing changes of 5-10% to be measured using SPM [58], as proven here.…”
Section: Discussionmentioning
confidence: 63%
“…In the design of this study, we have explicitly set the aim to investigate CB 1 receptor network alterations by using both absolute and relative [ 18 F]MK-9470 measurements. It is known that there is a higher physiologic interindividual variability of absolute regional [ 18 F]MK-9470 determinations in the human brain, in the order of several tens of per cent [14,57]. Relative measurements have the advantage of being much more sensitive, allowing changes of 5-10% to be measured using SPM [58], as proven here.…”
Section: Discussionmentioning
confidence: 63%
“…There are more convincing results on the association of the CNR1 gene and substance abuse disorders (Zhang et al, 2004;Zuo et al, 2007;Chen et al, 2008), although there is a negative replication study (Herman et al, 2006). Regarding depression, two studies with significantly smaller sample sizes failed to find any association with depression using the (AAT) n polymorphism (Barrero et al, 2005;Tsai et al, 2001), although the former found that a significant association emerged when only the depressed patients with Parkinson's disease were considered (Barrero et al, 2005).…”
Section: Introductionmentioning
confidence: 94%
“…Em relação à estratégia de avaliação e/ou obtenção de informações a respeito da presença de depressão nos pacientes com DP (Tabelas 2 e 3), os estudos foram organizados de acordo com o emprego de: a) entrevista clínica 8,13,14,[18][19][20][21][22] ; b) instrumentos estruturados de auto-avaliação [8][9][10]14,17,[23][24][25] ; c) entrevista clínica e instrumentos de auto-avaliação 11 ; e d) consulta em banco de dados 12,15,16,26 .…”
Section: Fontes De Dados E Instrumentos De Coleta De Informaçõesunclassified
“…Dos estudos selecionados, 11 10,11,13,14,17,18,[21][22][23][24]27 descrevem a relação entre a presença de depressão ou sintomas depressivos e os sintomas motores. Em todos os estudos, constatou-se correlação positiva entre piora do quadro motor, medida por escalas neurológicas específicas, e presença de depressão, corroborando a hipótese de que, ao comparar pacientes deprimidos e não deprimidos, o quadro motor é mais grave na presença de sintomas depressivos.…”
Section: Depressão E Sintomas Motoresunclassified
See 1 more Smart Citation